Kemampuan Siswa Kelas VII SMP Negeri 20 Kupang dalam Menulis Teks Eksposisi - Ndau, Dionesia; Djuli, Labu; Pekuwali, Dian Sari Arindah (Jurnal Lazuardi, 2025)
The focus of this study is How well do seventh-grade students at SMP Negeri 20 Kupang write expository texts? The purpose of this study is to analyze the ability of seventh-grade students at SMP Negeri 20 Kupang to write expository texts. The theory used is writing theory, because what is measured in this study is the students' ability to write expository texts based on their own reasoning skills and knowledge gained through social interaction. The method used in this study is descriptive qualitative. In this study, the researcher chose material about expository texts by considering the structure and linguistic aspects of expository texts. Expository texts are texts that contain explanations of information or knowledge based on facts about a particular topic presented in written form. Based on the results of the analysis conducted on 23 students in class VII A of SMP Negeri 20 Kupang, the ability to write expository texts with attention to the structure and linguistic aspects of expository texts can be said to be quite capable because 73% (17 students) were able to write fantasy texts with a score of 70-100. This is evidenced by the percentage of students who passed or achieved a minimum passing grade of 70 or above, totaling 17 students with a percentage of 73.91%, while the number of students who did not pass was 6 students with a percentage of 26.86%.